Ruang Terbuka Hijau Dan Permasalahan Kesehatan Perkotaan Studi Kasus Di Provinsi Dki Jakarta - SYAHADAT, RAY MARCH; PUTRA, PRIAMBUDI TRIE; PRATIWI, MADE DWI (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017DO - 10.24843/JAL.2017.v03.i02.p07, 2017)
This article aims to describe the role of green open space from landscape architecture views. The research conducted in Special Capital Region of Jakarta as the case study in order to solve the health issue. Case study approach was used in this research, include the primary and secondary data from literature view and projection calculation. Green open space has important role to solve the urban health problem caused by the pollutant. The result of this study shows that in 2017 Jakarta needs approximately 291,592 ha of green open space. There was several options that can be used to raise the quality of public health with limited area: (1) the using of effective vegetation to reduce the pollutant; (2) utilization of home garden; (3) vertical greenery implementation; (4) utilization of indoor garden; and (5) maintain the existence of city parks.